Glycan Stimulation Enables Purification of Prostate Cancer Circulating Tumor Cells on PEDOT NanoVelcro Chips for RNA Biomarker Detection. Issue 3 (11th September 2017) - Shen, Mo‐Yuan; Chen, Jie‐Fu; Luo, Chun‐Hao; Lee, Sangjun; Li, Cheng‐Hsuan; Yang, Yung‐Ling; Tsai, Yu‐Han; Ho, Bo‐Cheng; Bao, Li‐Rong; Lee, Tien‐Jung; Jan, Yu Jen; Zhu, Ya‐Zhen; et al.
Abstract: A glycan‐stimulated and poly(3, 4‐ethylene‐dioxythiophene)s (PEDOT)‐based nanomaterial platform is fabricated to purify circulating tumor cells (CTCs) from blood samples of prostate cancer (PCa) patients. This new platform, phenylboronic acid (PBA)‐grafted PEDOT NanoVelcro, combines the 3D PEDOT nanosubstrate, which greatly enhances CTC capturing efficiency, with a poly(EDOT‐PBA‐ co ‐EDOT‐EG3) interfacial layer, which not only provides high specificity for CTC capture upon antibody conjugation but also enables competitive binding of sorbitol to gently release the captured cells. CTCs purified by this PEDOT NanoVelcro chip provide well‐preserved RNA transcripts for the analysis of the expression level of several PCa‐specific RNA biomarkers, which may provide clinical insights into the disease. Abstract : A glycan‐stimulated and poly(3, 4‐ethylene‐dioxythiophene) (PEDOT)‐based nanomaterial platform is fabricated to purify circulating tumor cells. This PEDOT NanoVelcro chip not only provides highly efficient and specific capture of cancer cells but also enables competitive binding of glycan with higher affinity (i.e., sorbitol) to release them. Cancer cells purified are further utilized to correlate disease‐related RNA biomarkers in prostate cancer patients.